2020
DOI: 10.1002/term.3117
|View full text |Cite
|
Sign up to set email alerts
|

Portal venous repopulation of decellularised rat liver scaffolds with syngeneic bone marrow stem cells

Abstract: Liver transplantation is the only life-saving treatment for end-stage liver failure but is limited by the organ shortage and consequences of immunosuppression. Repopulation of decellularised scaffolds with recipient cells provides a theoretical solution, allowing reliable and timely organ sourcing without the need for immunosuppression. Recellularisation of the vasculature of decellularised liver scaffolds was investigated as an essential prerequisite to the survival of other parenchymal components. Liver dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The recellularized organ was cultured for 30 days. The cells showed markers for hepatic sinusoidal endothelial cells (mannose, Fc, and stabilin receptors), along with cell alignment reminiscent of the endothelium (Harper et al, 2020). Alternatively, many mechanisms have been proven concerning the role of MSCs as a paracrine factory in promoting angiogenesis (Caplan and Dennis, 2006).…”
Section: Mscs and Msc-derived Endothelial Cellsmentioning
confidence: 99%
“…The recellularized organ was cultured for 30 days. The cells showed markers for hepatic sinusoidal endothelial cells (mannose, Fc, and stabilin receptors), along with cell alignment reminiscent of the endothelium (Harper et al, 2020). Alternatively, many mechanisms have been proven concerning the role of MSCs as a paracrine factory in promoting angiogenesis (Caplan and Dennis, 2006).…”
Section: Mscs and Msc-derived Endothelial Cellsmentioning
confidence: 99%
“…Repopulation of decellularised livers : Repopulation of decellularised liver scaffolds with cells has offered a further refinement to the in vitro investigation of liver regeneration as well as potential therapeutic opportunities[ 118 ].…”
Section: Section 1: Models Of Liver Regenerationmentioning
confidence: 99%
“…Others have demonstrated that implanting repopulated ECM liver scaffolds into rats which had undergone extended hepatectomy improved liver function and extended their mean lifespan from 16 to 72 h[ 128 ]. In the last 10 years, a variety of animal models, decellularisation techniques, repopulation routes and cell sources have been described, with promising outcomes in terms of vascular repopulation[ 118 , 129 , 130 ], hepatocyte survival[ 131 ] as well as formation of biliary duct-like structures and activation of liver detoxification enzymes[ 132 ]. One of the commonest sources of liver scaffolds is the rat[ 118 , 127 , 132 - 137 ] repopulated with rat hepatocytes (although cholangiocytes[ 136 ] and lineages from pluripotent stem cells, mesenchymal cells, and fibroblasts have also been described[ 137 ] usually via the portal vein.…”
Section: Section 1: Models Of Liver Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cell types could be used for repopulating decellularized livers, including primary hepatocytes, iPSCderived hepatocyte-like cells, stem cells, or mesenchymal stromal cells for recellularization of the parenchymal areas, and endothelial progenitor cells or human umbilical vein endothelial cells (HUVEC) for reendothelization [85,[128][129][130][131][132]. However, optimization of the recellularization process is still a challenge when more than one cell type per scaffold is used.…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%